Integrated Analysis of LncRNA-mRNA Coexpression in the Extracellular Matrix of Developing Deciduous Teeth in Miniature Pigs. (23rd January 2019) - Li, Yang; Li, Guoqing; Wang, Fu; Wu, Xiaoshan; Wu, Zhifang; Wang, Jinsong; Zhang, Chunmei; He, Junqi; Wang, Hao; Wang, Songlin
Abstract : Miniature pigs, a valuable alternative model for understanding human tooth development, have deciduous teeth from all four tooth families that are replaced once by permanent molars. The extracellular matrix (ECM) supports cells and maintains the integrity of tooth germs during tooth development. However, details on the role of the ECM in tooth development are poorly understood. Here, we performed long noncoding RNA (lncRNA) and messenger RNA (mRNA) expression profiles in the ECM components of deciduous tooth germs by RNA sequencing in miniature pigs. From the early cap to the late bell stages, we identified 4, 562 and 3, 238 differentially expressed genes (DEGs) from E40 to E50 and E50 to E60, respectively. In addition, a total of 1, 464 differentially expressed lncRNAs from E40 to E50 and 969 differentially expressed lncRNAs from E50 to E60 were obtained. Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway analysis showed that DEGs were enriched significantly for multiple signaling pathways, especially for the ECM pathway. We then outlined the detailed dynamic gene expression profiling of ECM components during deciduous molar development. Comparison of the cap and bell stages revealed that the structure and functions of the ECM dynamically changed. The ECM-related genes, including THBS1, COL4A5, COL4A6, COL1A1, CHAD, TNR, GP1BA, and ITGA3, were significantly changed, and some were shown to enrich during the bell stage development. Finally, we outlined the coexpression of lncRNAs and ECM properties during tooth development. We showed that the interplay of key lncRNAs could change ECM processes and influence the ECM establishment of tooth patterns to accomplish full tooth formation. These results might provide information to elucidate the regulation network of the lncRNA and ECM in tooth development.